PERGESERAN MAKNA ESENSI WALIMATUL ‘URS - Annas Muhtadin; Rina Antasari; Nurmala HAK (Program Studi Al-Ahwal Al-Syakhshiyyah, 2022)
The form of the marriage ceremony in Islam is commonly known as walimah al-urs. The Qur'an does not mention the implementation of walimah al-urs, but only recommends getting married. In the past, the wedding party was enough to invite neighbors and family. Usually the family who will be the witnesses attend a very historic event for the bride and groom, accompanied by reading the Koran, prayers and praise of gratitude to Allah SWT. However, at this time the implementation of walimah al-urs has undergone a change or a shift that is almost out of the goal of walimah al-urs itself, it has become a common culture that a wedding or walimah al-urs must be luxurious, starting from giving dowries and holding a big party. -size and so on. This is what happened in the community of Pedamaran District, Ogan Komering Ilir Regency. This research is classified as field research with empirical normative research methods. Based on the results of the study, it was concluded that walimah al-urs or wedding parties in Pedamaran District, Ogan Komering Ilir Regency had become a tradition or habit and had even become a necessity whose implementation was related to the holding of a marriage. The initial goal of the people of Pedamaran District, Ogan Komering Ilir Regency in walimah al-urs was very good, namely to please children and to entertain invited guests and as an expression of gratitude, but in practice it has experienced a shift and the resulting impact is social jealousy between communities, used to gain profit (business), the nature of prestige, disturbing the peace caused by the community. Keywords: Walimah Al-Urs; Sociology; Family Law